Laboratory Landquakes: Insights From Experiments Into the High‐Frequency Seismic Signal Generated by Geophysical Granular Flows. Issue 5 (14th May 2021) - Arran, M. I.; Mangeney, A.; De Rosny, J.; Farin, M.; Toussaint, R.; Roche, O.
Abstract: Geophysical granular flows exert basal forces that generate seismic signals, which can be used to better monitor and model these severe natural hazards. A number of empirical relations and existing models link these signals' high‐frequency components to a variety of flow properties, many of which are inaccessible by other analyses. However, the range of validity of the empirical relations remains unclear and the models lack validation, owing to the difficulty of adequately controlling and instrumenting field‐scale flows. Here, we present laboratory experiments investigating the normal forces exerted on a basal plate by dense and partially dense flows of spherical glass particles. We measured the power spectra of these forces and inferred predictions for these power spectra from the models for debris flows' seismic signals proposed by Kean et al. (2015, https://doi.org/10.1002/2015GL064811 ), Lai et al. (2018, https://doi.org/10.1029/2018GL077683 ), and Farin, Tsai, et al. (2019, https://doi.org/10.1002/esp.4677 ), using Hertz theory to extend Farin, Tsai, et al. (2019)'s models to higher frequencies. Comparison of our observations to these predictions, and to predictions derived from Bachelet (2018) and Bachelet et al. (2021)'s model for granular flows' seismic signals, shows those of Farin, Tsai, et al. (2019)'s "thin‐flow" model to be the most accurate, so we examine explanations for this accuracy and discuss its implications for geophysical flows' seismic signals. We also consider the normalization, by the mean force exerted by each flow, of the force's mean squared fluctuations, showing that this ratio varies by 4 orders of magnitude over our experiments, but is determined by the bulk inertial number of the flow. Plain Language Summary: Landslides, like earthquakes, generate seismic signals: vibrations of the earth that can be detected a long way away. Analysis of the most rapid vibrations could provide information about how large a landslide is or how damaging it will be, helping emergency services respond. But full‐size landslides are complex and difficult to study, so the generation of these vibrations is not yet sufficiently well understood for this information to be reliable. Therefore, in the place of full‐size landslides, we studied simplified, small‐scale versions in the laboratory, testing previous authors' predictions for the seismic signals they generate. We find that one set of predictions was particularly accurate and show that the corresponding predictions for full‐size landslides are consistent with previous observations. This implies that a landslide's seismic signal can be used to calculate its size, its speed, and the typical size of particles within it. Key Points: We conducted novel laboratory experiments to test five existing models for the high‐frequency seismic signals generated by granular flows The "thin‐flow" model of Farin, Tsai, et al. (2019, https://doi.org/10.1002/esp.4677 ) was the most accurate and makes predictions consistent with empirical observations The ratio between the mean and fluctuating forces exerted by a granular flow varies greatly, determined by an inertial number of the flow